2022
DOI: 10.1038/s41598-022-25439-0
|View full text |Cite|
|
Sign up to set email alerts
|

Pan-cancer analysis based on epigenetic modification explains the value of HJURP in the tumor microenvironment

Abstract: To analyze the expression levels, prognostic value and immune infiltration association of Holliday junction protein (HJURP) as well as its feasibility as a pan-cancer biomarker for different cancers. The Protter online tool was utilized to obtain the localization of HJURP, then the methylation of HJURP in tumors were further explored. Thereafter, the mRNA data and clinical characteristics of 33 tumor types from TCGA database were obtained to investigate the expression and prognostic relationship of HJURP in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…For example, in U2OS cells, serous ovarian cancer cells, and t(4;14)-positive multiple myeloma cells, HJURP has been observed to localize in the nucleus [8,9,12,72]. HJURP has been further found to co-localize with ER and microtubules in U2OS cells [15]; however, in various cancer cells, including HCC, and prostate and breast cancers, HJURP is mainly expressed in the cytoplasm [34,48,53,54]. HJURP has been located in the cytoplasm and/or cell membrane in CRC [41], while in gliomas HJURP immunoreactivity has been observed in both the nucleus and cytoplasm, increasing with the grade of gliomas [64].…”
Section: Summary and Perspectivesmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, in U2OS cells, serous ovarian cancer cells, and t(4;14)-positive multiple myeloma cells, HJURP has been observed to localize in the nucleus [8,9,12,72]. HJURP has been further found to co-localize with ER and microtubules in U2OS cells [15]; however, in various cancer cells, including HCC, and prostate and breast cancers, HJURP is mainly expressed in the cytoplasm [34,48,53,54]. HJURP has been located in the cytoplasm and/or cell membrane in CRC [41], while in gliomas HJURP immunoreactivity has been observed in both the nucleus and cytoplasm, increasing with the grade of gliomas [64].…”
Section: Summary and Perspectivesmentioning
confidence: 97%
“…Abnormal upregulation of HJURP has been demonstrated in various human cancers based on public genomics databases and independent patient cohorts. Two pan-cancer analyses were performed to determine the relationship between HJURP and cancer [14,15]. Specifically, these studies showed that HJURP expression is upregulated in most human cancers.…”
Section: Expression Of Hjurp In Cancersmentioning
confidence: 99%
See 1 more Smart Citation